Dakwah Islam Dan Budaya Lokal (Sebuah Upaya Pemurnian Ajaran Islam) - Akhirudin Akhirudin; Ahmad Syaefuddin (Sekolah Tinggi Agama Islam Publisistik Thawalib Jakarta, 2022)
Among the interesting phenomenon in recent years, especially in the last two or three decades, is a growing interest in religious life. The amount of interest in the religious life of course invited religious organizations to examine the existence of religious life, namely in the context of the role of Islam as rahmatan lil 'alamin. Religion in relation as cultural products will be reflected in both the form and the content of the culture. Apparently, ethnic diversity and religious understanding diversity is reflected in the form of culture. Ideas, activities and cultural objects visible in the community is not one and the same. Factors facto as noted above, the factors that drove the cultural diversity of form and content reflected in social phenomena. Among the residents of the ethnic communities themselves.